The Influence of Project-Based Learning (PJBL) Model on Holistic Learning Outcomes in Plant Classification at SMP Asy-Syarifiy - Khosyillah, Mochamad; Khusnah, Laila (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
This study aims to analyze the effect of the Project Based Learning (PJBL) model on the holistic learning outcomes of seventh-grade students in the plant classification topic at SMP Asy-Syarifiy IEBS Lumajang. The PJBL model was implemented through a herbarium-making project designed to enhance students’ active engagement in learning and to develop cognitive, affective, and psychomotor skills in a balanced manner. This research employed a quantitative approach with a post-test only control group design. The results indicate that the implementation of PJBL has a significant effect on students’ holistic learning outcomes compared to conventional teaching methods. Through participation in real-life projects, students demonstrated improved understanding of plant classification concepts, teamwork skills, and the expression of values and attitudes toward the environment. Therefore, PJBL has been proven effective in supporting comprehensive and contextual learning achievements.